The overdamped limit of dynamic density functional theory: Rigorous results - Goddard,BD; Pavliotis,GA; Kalliadasis,S (MULTISCALE MODELING & SIMULATION, 2012)
Consider the overdamped limit for a system of interacting particles in thepresence of hydrodynamic interactions. For two-body hydrodynamic interactionsand one- and two-body potentials, a Smoluchowski-type evolution equation isrigorously derived for the one-particle distribution function. This newequation includes a novel definition of the diffusion tensor. A comparison withexisting formulations of dynamic density functional theory is also made.